(untitled) (Konferensiyalar | Conferences, 2024)
This study is intended to provide a brief overview of creative strategies and modules for English language learners, so we offered higher education students and senior students their experiences and insights on this topic. The design of this study is qualitative-descriptive and analytical, which makes it easy to understand the importance of creativity and ways of promoting new ideas in a foreign or selected language. In addition, the main purpose of this article is to determine the importance of introducing new ideas in language and speech. In other words, it summarizes a number of proven complex strategies that illustrate how to take a positive approach to common problems in this sphere.